2011
DOI: 10.1016/j.neulet.2011.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Central orexin-A increases colonic motility in conscious rats

Abstract: Increasing evidence has indicated that brain orexin plays a vital role in the regulation of gastrointestinal physiology such as gastric secretion, gastric motility and pancreatic secretion. However, little is known whether orexin in the brain is involved in the physiology of the lower gastrointestinal tract. The aim of this study was therefore to elucidate whether orexin-A in the brain is involved in the regulation of colonic motility. In this study, we measured fecal pellet output and recorded intraluminal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The present data clearly demonstrated that ip injection of orexin-A failed to stimulate gastric motility, strongly confirming that ic orexin-A acts centrally in the brain to stimulate gastric motility in freely moving conscious rats. We have very recently demonstrated that ic injection of orexin-A significantly enhanced colonic motor function in conscious rats [22]. The present study therefore provides evidence that orexin-A in the brain stimulates not only colonic but also gastric contractility in conscious rats.…”
Section: Discussionsupporting
confidence: 73%
“…The present data clearly demonstrated that ip injection of orexin-A failed to stimulate gastric motility, strongly confirming that ic orexin-A acts centrally in the brain to stimulate gastric motility in freely moving conscious rats. We have very recently demonstrated that ic injection of orexin-A significantly enhanced colonic motor function in conscious rats [22]. The present study therefore provides evidence that orexin-A in the brain stimulates not only colonic but also gastric contractility in conscious rats.…”
Section: Discussionsupporting
confidence: 73%
“…OXA stimulates gastric acid secretion throughout vagal pathways [46], regulates intestinal bicarbonate secretion [32], and gastrointestinal and colon motility [33], [35], [47]. Studies on the dose-dependent peripheral effects of OXA and OXB on intestinal wall show that they slow down intestinal motility by extending of duration of migrating motor complex (MMC) [22,23,48 7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a key role in food intake, orexins are also involved in the control of several biological functions such as arterial blood pressure and heart rate [24], sleep/wake cycle [25], water assumption [26], plasma corticosteroid levels [27], testosterone production [28], and endocrine and exocrine pancreatic secretions [29][31]. A series of recent studies [32][35] proposed a role of the orexin system in the central and peripheral control of gastrointestinal secretion and motility.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the role of central orexin in digestive functions, it has been reported that orexin acts in the brain to stimulate gastric and pancreatic secretion, and increase gastric and colonic motility in rats (Takahashi et al, 1999;Okumura et al, 2001;Yamada et al, 2005;Nozu et al, 2011;Nozu et al, 2012;Bülbül et al, 2010a and2010b;Kobashi et al, 2002;Krowicki et al, 2002;Miyasaka et al, 2002). The present study therefore provided a novel evidence that central orexin plays a role in not only gastrointestinal secretion and motility but also gut sensation.…”
Section: Discussionmentioning
confidence: 99%